WEB CURRICULUM AND DISTANCE EDUCATION: CURRICULAR PATHWAYS MEDIATED BY DIGITAL TECHNOLOGIES - Fonseca Junior, Anderson; Soares, Diego Ricardo Lima; Fonseca, Kayõ de Luna (Seven Editora, 2025)
This article analyzes the characteristics, potentialities, and challenges of the Web Curriculum in the context of Distance Education (DE), in light of the transformations brought about by digital culture. This bibliographic research is based on academic works, scientific articles, and official documents, aiming to understand how curricula mediated by digital technologies can promote more meaningful, interactive, and inclusive learning. Initially, the evolution of the curriculum concept and its social function is discussed, highlighting the transition from traditional models to more critical and flexible approaches. Then, the specificities of DE and the curricular models that support it are explored, emphasizing pedagogical mediation and personalized learning. The Web Curriculum is presented as an innovative proposal, grounded in principles such as hypertextuality, authorship, and collaboration, aligning with active methodologies and the demands of networked society. The discussion reveals both the advantages and the challenges of this approach, including digital exclusion, teacher training, and assessment in DE. It is concluded that the effective implementation of the Web Curriculum requires public policies, adequate infrastructure, and continuous teacher development, as well as new pedagogical practices that value autonomy and authorship in digital culture. DOI: https://doi.org/10.56238/sevened2025.038-045